2017
DOI: 10.1189/jlb.2ma0117-019r
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cell surface 90 kDa heat shock protein (HSP90) in pattern recognition by human monocyte-derived macrophages

Abstract: Heat shock proteins (HSPs) are typical intracellular chaperones which also appear on the cell surface and in extracellular milieu. HSP90, which chaperones many proteins involved in signal transduction, is also a regular component of LPS-signaling complexes on Mϕ. As LPS is a prototypical PAMP, we speculated that HSP90 is engaged in pattern recognition by professional phagocytes. In this report, we provide the first evidence, to our knowledge, of the geldanamycin (Ge)-inhibitable HSP90 on the surface of live mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In one study, following exposure to LPS, the sequential activation of SIRT1 and SIRT3 was found to integrate the induction of mitochondrial biogenesis with the down-regulation of pro-inflammatory responses ( 36 ). Another potential link between immunity and mitochondrial homeostasis is suggested by findings that the intracellular chaperone heat shock protein-90 (HSP90) is both essential for effective clearance of defective mitochondria by mitophagy and implicated, through accumulation at the cell surface, in the suppression of TNFα production in response to LPS ( 70 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, following exposure to LPS, the sequential activation of SIRT1 and SIRT3 was found to integrate the induction of mitochondrial biogenesis with the down-regulation of pro-inflammatory responses ( 36 ). Another potential link between immunity and mitochondrial homeostasis is suggested by findings that the intracellular chaperone heat shock protein-90 (HSP90) is both essential for effective clearance of defective mitochondria by mitophagy and implicated, through accumulation at the cell surface, in the suppression of TNFα production in response to LPS ( 70 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are presumably many undiscovered fuels and signals associated with tumors involved in metabolic alterations and polarization in macrophages. Other mechanisms by which tumor‐associated macrophage differentiation may be facilitated are highlighted by the caspase‐dependent cleavage of peroxisome PPAR‐γ, which results in the inhibition of fatty acid oxidation and accumulation of tumor associated macrophage (TAM)‐promoting lipid droplets Another intriguing mechanism by which tumors may influence phagocyte metabolism is by alterations in expression or function by cell surface proteins, such as HSP90 . Although HSP90 is a typical cytoplasmic/nuclear chaperone protein capable of regulating mitophogy and cytokine production in macrophages, it also comprises a pool of cell surface associated proteins potentially regulated by extracellular cues such as tumors.…”
Section: Functional Diversity In Phagocytic Cellsmentioning
confidence: 99%
“…In addition, repression of pro-inflammatory cytokine from macrophage reduced the damage of AKI (43). For example, heat shock protein (HSP) 90 is associated with pro-inflammatory cytokine production of monocyte and macrophage and its inhibition reduced the damage of AKI (44,45). Macrophages have two distinct phenotypes and functions, and their polarization is regulated by the surrounding microenvironment (46,47).…”
Section: Discussionmentioning
confidence: 99%